An advanced 10K SNP panel for genotyping tomato (Solanum lycopersicum L.) via targeted genome sequencing - Adedze, Yawo Mawunyo Nevame; Xu, Yanfen; Liu, Song; Zhao, Yaran; Mo, Changjuan; Zhang, Renxu; Dong, Jiahui; Lan, Haofa; Huang, Jingjing; Chen, Xingming; Gao, Xuefei; Yin, Qingzhen; et al. (Frontiers in Plant Science, 2025)
IntroductionRecent breakthroughs in genomics have facilitated the identification of single nucleotide polymorphisms (SNPs) and small insertions-deletions (InDels). With the reduction in sequencing costs, a variety of genotyping tools have emerged for genetic analysis in plants. However, there is a significant need for an effective and affordable tool that combines both foreground and background sites.MethodsTo meet this requirement in tomatoes, four SNP databases accounting for 12,442 SNPs were integrated with 186 trait-specific markers. A total of 335 tomato samples were used for the genotyping by target sequencing analysis. A series of criteria were performed for site selection and for assessing the sequencing data effectiveness.Results and discussionThe panel designated as the GenoBaits Tomato 10K panel ultimately comprised 11,174 background sites, with 74.83% sourced from database 1 upon optimization. The uniformity_50 and capture efficiency of this panel were 98.03% and 74.84%, respectively, while the SNP detection rate was 99.34%. The SNPs with a minor allele frequency (MAF) > 0.05 accounted for 60.57%, and those with MAF > 0.4 represented 20%. The average genome MAF was 0.18, with a gap value of 0.07 Mbp. The GenoBaits Tomato 10K panel has demonstrated its effectiveness in assessing genetic diversity, with minimal impact from trait-specific markers. This panel effectively pinpointed the predefined resistant and susceptible marker alleles associated with 19 key tomato resistance genes in the targeted population. Therefore, future research should validate them in order to unlock the full diagnostic potential of this panel in tomato genetics and breeding.